2006
DOI: 10.1017/s0265021506001025
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring cerebral oxygen saturation in elderly patients undergoing general abdominal surgery: a prospective cohort study

Abstract: In a population of healthy elderly patients, undergoing non-vascular abdominal surgery cerebral desaturation can occur in up to one in every four patients, and the occurrence of cerebral desaturation is associated with a higher incidence of early postoperative cognitive decline and longer hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 22 publications
4
97
2
2
Order By: Relevance
“…Cerebral saturation has been examined as a functional monitor for cerebral ischemia and major organ dysfunction in cardiac, major abdominal, and carotid surgery. [10][11][12]14,24 It generally compares favourably with other monitors of cerebral ischemia, such as transcranial Doppler, somatosensory evoked potentials, and stump pressure during carotid cross-clamp. 14,[25][26][27] Although no cutoff value has been universally agreed on, 28 a 20% decrease in rSO2 has been suggested as a suitable threshold value to detect cerebral ischemia (sensitivity 80% and specificity 82%) with a primarily high negative predictive value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral saturation has been examined as a functional monitor for cerebral ischemia and major organ dysfunction in cardiac, major abdominal, and carotid surgery. [10][11][12]14,24 It generally compares favourably with other monitors of cerebral ischemia, such as transcranial Doppler, somatosensory evoked potentials, and stump pressure during carotid cross-clamp. 14,[25][26][27] Although no cutoff value has been universally agreed on, 28 a 20% decrease in rSO2 has been suggested as a suitable threshold value to detect cerebral ischemia (sensitivity 80% and specificity 82%) with a primarily high negative predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…9 It has been evaluated as a monitor for cerebral ischemia in multiple clinical settings, and in some instances, it can predict the risk of cognitive decline and length of hospital stay. [10][11][12] At our institution, controlled hypotension in the sitting position is commonly performed for patients undergoing ambulatory shoulder arthroscopy. We prospectively measured blinded rSO2 in patients undergoing ambulatory shoulder arthroscopy in the sitting position to determine the incidence of rSO2 desaturation.…”
Section: Résumémentioning
confidence: 99%
“…Even short episodes of reduced brain saturation below 65%, which were observed in more than half of patients, were associated with a two-fold higher incidence of consciousness disorders. Additionally, elderly patients with restored proper values of brain saturation showed lower incidences of cognitive dysfunctions and required shorter ICU treatment [30].…”
Section: Use Of Brain Oximetry In Other Surgical Fieldsmentioning
confidence: 97%
“…Tang and colleagues [29] have observed a relationship between low values of brain saturation and cognitive dysfunctions in the early postoperative period following the procedures with onelung ventilation. Moreover, patients with a decrease in brain saturation by at least 25% were hospitalized substantially longer [30]. Even short episodes of reduced brain saturation below 65%, which were observed in more than half of patients, were associated with a two-fold higher incidence of consciousness disorders.…”
Section: Use Of Brain Oximetry In Other Surgical Fieldsmentioning
confidence: 99%
“…3 In addition, previous studies have reported that it causes a significant reduction of cerebral tissue oxygen saturation (Sct O 2 ) in elderly patients 4 and in patients with pre-existing raised intracranial pressure (ICP). 5 Patients presenting for robotic surgery are usually elderly, and are thus patients in whom the procedure may upset the critical balance between cerebral oxygen supply and demand.…”
mentioning
confidence: 99%